Intra-Facility Acquisition of Methicillin-Resistant Staphylococcus aureus (MRSA) in Southern Wisconsin Skilled Nursing Facilities. (4th October 2017) - Palmer, Samuel; Duster, Megan; Warrack, Simone; Zehm, April; Filas-Mortensen, Patricia; Crnich, Christopher
Abstract: Background: Studies have shown that skilled nursing facilities (SNFs) are reservoirs for methicillin-resistant Staphylococcus aureus (MRSA). The extent to which resident-to-resident transmission accounts for the high burden of MRSA in these facilities remains poorly understood. The objective of this study was to estimate the frequency of intra-facility MRSA acquisition in a sample of SNFs participating in a longitduinal study in Wisconsin. Methods: MRSA colonization among a cohort of 449 subjects residing in six SNFs in Southern Wisconsin was measured using serial, multi-anatomical surveillance culturing. Phenotypic acquisitions events (i.e., MRSA [-] to MRSA[+]) were identified and further characterized both temporally (calendar date) and genetically (pulse-field gel electrophoresis). An intra-facility acquisition event was defined as incident recovery of an MRSA isolate that was genetically identical to at least one other strain previously recovered in a study facility. A Marascuilo procedure for comparing multiple proportions was employed to determine whether the proportion of intra-facility MRSA acquisitions differed across study facilities. Linear regression was employed to assess if certain facility-level characteristics were associated with rates of intra-facility MRSA acquisition. Results: 129 acquisition events were identified that met our criteria, of which 74 were determined to be intra-facility (57.4%) [95% CI: 45.5–67.6%]. Statistically significant differences were found between the intra-facility acquisition proportion of multiple SNFs. A facility's baseline MRSA prevalence was significantly associated with its intra-facility MRSA acquisition rate (R 2 = 0.784, P- value = 0.012). Conclusion: Intra-facility acquisition represents a large proportion of the burden of MRSA observed in SNFs. The rate of intra-facility acquisition is variable between facilities but may, in part, be explained by the prevalent burden of MRSA in the facility (i.e., MRSA colonization pressure to characteristics of the facility). Whether other facility characteristics, including infection prevention practices are contributing to these transmission dynamics requires further study. Disclosures: All authors: No reported disclosures.